Board leadership structure, board remuneration and firm size to firm profitability of top 100 FTSE Bursa Malaysia index companies / Azbariyah Ajit @ Abd Aziz - Ajit@Abd Aziz, Azbariyah (2012)
This paper examines the interrelation between board leadership structure, board remuneration and firm size to firm profitability in a sample of top 100 FTSE Bursa Malaysia Index listed companies. The two board leadership structures examined in this study are size and role duality. This paper also examined board remuneration and firm size as independent variables controlling by leverage. The data are gathered from the analysis of annual report for companies listed in the Bursa Malaysia, beginning from the year 2007 until 2010. Multiple regressions are applied to test the significance of board leadership structures, board remuneration and firm size to firm profitability. The result shows that all independent variables do not have a significant relationship with the firm profitability.